Visionary Leadership of School Principals in Enhancing the Quality of Education - Anas, Iqbal; Sesmiarni, Zulfani; Sunani, Eneng; Ahmed, Abdal; Ibad, Akhmad Zaenul (Thawalib: Jurnal Kependidikan Islam, 2025)
Visionary leadership of school principals plays a critical role in enhancing the quality of education through strategic vision, teacher supervision, instructional innovation, and collaboration among all stakeholders to create a favourable school climate. This study aims to analyze the role of visionary leadership in improving educational quality and to develop an effective contextual leadership model for the first secondary school, Muhammadiyah Payakumbuh. The research employed a qualitative case study approach, utilizing data collection techniques including semi-structured interviews, observations, and document analysis. Data were analyzed iteratively through data reduction, presentation, and concluding. Data validation was conducted through the triangulation of sources, methods, and time to ensure the consistency and accuracy of the findings. Results indicate that the principal has formulated a clear educational vision and begun its implementation through programs to improve learning, strengthen character development, and enhance teacher capacity. Visionary leadership is characterised in collaborative strategies, effective stakeholder engagement, and seamless technology integration. Positive impacts are evident in improved student learning outcomes and increased parental satisfaction. However, challenges such as limited budget, teacher resistance, and infrastructure constraints remain obstacles. This study highlights the importance of visionary leadership, stakeholder support, and continuous training in achieving sustainable educational quality in resource-limited schools. In conclusion, visionary leadership is essential for improving educational quality, but its success heavily depends on the collective support of all stakeholders.